Highly Microcrystalline Phosphorous‐Doped Si:H Very Thin Films Deposited by RF‐PECVD. Issue 13 (14th May 2022) - Wilson, Alestair; Fourmond, Erwann; Saidi, Bilel; Fornacciari, Benjamin; Brottet, Solène; Juhel, Marc; Gros-Jean, Mickael
Abstract : Fine‐tuning the crystallinity and doping of the hydrogenated microcrystalline silicon thin films are the key points in obtaining high‐quality devices for above‐integrated circuit (above‐IC) image sensors. This study focuses on the structural and electrical properties of radio‐frequency plasma enhanced chemical vapor deposition (RF‐PECVD) deposited microcrystalline silicon (μc‐Si:H) contact layers. Herein, phosphorus‐doped μc‐Si:H is deposited by capacitively coupled plasma RF‐PECVD (13, 56 MHz) from a SiH4 + H2 + PH3 gas mixture with varying phosphine concentrations. The influence of phosphine concentration on dopant concentration, active dopant concentration, and crystallinity is studied by secondary ion mass spectrometry, Hall effect measurement, and Raman spectroscopy, respectively. A high doping level is attained, reaching up to 1.7 × 10 20 cm −3 . Furthermore, "low‐power" and "high‐power" deposition conditions are studied which lead to incubation layers of different nature. Abstract : Strongly doped n‐type microcrystalline silicon is obtained by PECVD, with doping levels reaching 1.7 × 10 20 cm −3 . The influence of gas‐phase phosphine (PH3 ) concentration on absolute dopant concentration, active dopant concentration, and disturbance of the crystalline‐phase nucleation is studied by SIMS, Hall effect measurement, and Raman spectroscopy in different deposition conditions.